Application of Machine Learning Methods for the Development of Antidiabetic Drugs - Zhao, Juanjuan; Xu, Pengcheng; Liu, Xiujuan; Ji, Xiaobo; Li, Minjie; Sooranna, Dev; Qu, Xiaosheng; Lu, Wencong; Niu, Bing (Current Pharmaceutical Design, 2022)
Diabetes is a chronic non-communicable disease caused by several different routes, which has attracted increasing attention. In order to speed up the development of new selective drugs, machine learning (ML) technology has been applied in the process of diabetes drug development and opens up a new blueprint for drug design. This review provides a comprehensive portrayal of the application of ML in antidiabetic drug use.
Keywords: hypoglycemic action